2020
DOI: 10.1111/bph.15027
|View full text |Cite
|
Sign up to set email alerts
|

Functional marriage in plasma membrane: Critical cholesterol level–optimal protein activity

Abstract: In physiology, homeostasis refers to the condition where a system exhibits an optimum functional level. In contrast, any variation from this optimum is considered as a dysfunctional or pathological state. In this review, we address the proposal that a critical cholesterol level in the plasma membrane is required for the proper functioning of transmembrane proteins. Thus, membrane cholesterol depletion or enrichment produces a loss or gain of direct cholesterol-protein interaction and/or changes in the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Other studies have suggested a role for cholesterol in the maturation, structure or function of integral plasma membrane proteins 177,178 . In particular, several G protein‐coupled receptors are regulated by the sterol 179,180 .…”
Section: Regulation Of Plasma Membrane Protein Activitymentioning
confidence: 99%
“…Other studies have suggested a role for cholesterol in the maturation, structure or function of integral plasma membrane proteins 177,178 . In particular, several G protein‐coupled receptors are regulated by the sterol 179,180 .…”
Section: Regulation Of Plasma Membrane Protein Activitymentioning
confidence: 99%
“…It is also the most important functionally-relevant non-phospholipid in human health and disease. Due to its unique structural features, cholesterol affects the physical properties of model and biological membranes ( Yeagle, 1985 ; Meza et al, 2020 ). It is quite established that the distribution of cholesterol in the cellular membranes is not uniform, rather there exists a cholesterol gradient, i.e ., cholesterol is present at ∼35–45 mol% in the plasma membrane and is severely depleted in intracellular membranes ( Yeagle, 1985 ; van Meer et al, 2008 ; Subczynski et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is often laterally associated with sphingolipids in plasma membranes to form lateral membrane heterogeneities called functional microdomains or ‘rafts’ that have been implicated in various functions in mammalian cells ( Lingwood and Simons, 2010 ; Rao and Mayor, 2014 ; Kusumi et al, 2023 ). Importantly, cholesterol is a major regulator of the function of different classes of membrane proteins like ion channels, transporters and G-protein coupled receptors through direct and indirect effects ( Levitan et al, 2014 ; Zakany et al, 2020 ; Meza et al, 2020 ; Taghon et al, 2021 ; Yeagle, 2022 ). Particularly, cholesterol affects the functional activity of voltage-gated (K v ), inward rectifier K + (Kir), and BK channels ( Levitan et al, 2014 ; Zakany et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These acute shifts in free cholesterol not only serve as homeostatic feedback signals to cytoplasmic effectors but also modulate the activity of numerous PM proteins. 7,9,11,59 8. We chose a value of K1 PM = 5000 for the sterol association constant of PM phospholipids with a stoichiometry of C:P = 1:1.…”
Section: The Concentration Of Cholesterol In Typicalmentioning
confidence: 99%